Analisis Semiotika Roland Barthes pada Representasi Makna Kehilangan Film “Generasi 90an: Melankolia” - Jakaria, M Ihsan; Mayasari., Mayasari.; Lubis, Flori Mardiani (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Film is a mass communication media tool that has a role in this era. Not only for entertainment but can be used as a medium of learning. Regardless of the development of technology and information that continues to develop, it has a similar impact on the development of film in the world. Film becomes a social discourse with unique characteristics that spread to various places, and a film psychoanalyst perspective to influence ways of thinking related to the perception and suitability of values where the information is communicated. Films in general also raise a theme or phenomenon that occurs in the midst of society. One such film is